One-pot production of oxygenated monomers and selectively oxidized lignin from biomass based on plasma electrolysis. Issue 22 (3rd November 2021) - A, Lusi; Radhakrishnan, Harish; Hu, Hui; Bai, Xianglan
Abstract : One-pot conversion of biomass is performed to produce carbohydrate-derived oxygenated monomers and a selectively oxidized lignin using a single-step process. Abstract : Herein, we report a novel method to obtain oxygenated chemicals and high-quality lignin from biomass in one-pot using a single step process. Plasma electrolysis of red oak was conducted by applying high-voltage alternating current electricity in γ-valerolactone using sulfuric acid as the electrolyte. Red oak was completely solubilized to produce levoglucosenone and furfural as the two major monomers with the respective yields of up to 44.9 mol% and 98.0 mol%. During the conversion, an oxidized lignin was also simultaneously produced in high purity. The valorization potential of the plasma electrolysis-derived lignin evaluated using the pyrolysis method showed that depolymerization of this lignin could produce significantly higher yields of phenolic monomers than the natural lignin or the lignin isolated during conventional solvolysis. Our investigation showed that benzylic carbon of the natural lignin was selectively modified during plasma electrolysis to limit the formation of interunit C–C bonds, significantly improving the subsequent lignin valorization to aromatic monomers. Overall, this study demonstrated a simple green approach to improve chemical production without using costly catalysts or tedious biomass fractionation. This study also presented a novel and highly efficient way to modify lignin for enhanced valorization.